SKRINING BAKTERI BERPOTENSI PENDEGRADASI POLIETILEN OXO-DEGRADABLE DARI TANAH GAMBUT DI SEKITAR TPA KUALA DUA RASAU JAYA - Firdaus, Nadhifah Rizqi; Rahmawati, Rahmawati; Riyandi, Riyandi (Universitas Tanjungpura, 2019)
The use of polyoethylene degradable polyethylene in Indonesia, especially in West Kalimantan, is high enough to potentially cause environmental pollution. One way to resolve pollution caused by polyethylene oxo-degradable plastic waste is to utilize isolates from the peat soil around the Kuala Dua Final Disposal Site, Rasau Jaya, which is able to degrade oxo-degradable polyethylene. This research aims to determine the bacterial genera that can to be expected to degrade Oxo-Degradable Polyethylene. Samples were taken from peat soil with the incubation method of oxo-degradable polyethylene for 2 weeks, 4 weeks and 6 weeks. Isolation use the pour plate method with Enrichment Broth Media and Enrichment Agar Media. The isolation results obtained 9 (nine) bacterial isolates which are distinguished based on incubation time and morphological characters.